Chinese Internet Media Development and Interpretation of the Theme of National Culture - Aminova, Dilnoza Khikmatilla Kizi (International Journal of Psychosocial Rehabilitation, 2020)
The development tendency of the Chinese Internet journalism is analyzed in this paper. Also, the impact of the three major state projects (“One country – two systems”, “One Space, One Road”, the implementation of the concept “Soft Power”) adopted in 2010 to Chinese journalism was analyzed separately. At the same time, the article analyzes the materials on the activity of Friendly Societies “Uzbekistan – China” and “The people’s Republic of China – Central Asian countries”, the National Cultural Center of China in Tashkent. The interpretation of the theme China on the internet media of Uzbekistan like “uza.uz”, “zarnews.uz”, “daily.uz”, “madaniyat.uz”, “xs.uz” and the comparative analysis of the leading Internet publications of the two countries, online publications “Khalq so’zi” and online publications “Jenmin jebao”, their common and different aspects have been scientifically-theoretically investigated in the present article.